Valorization of waste date pulp and seeds in sustainable fabrication of Al2O3 nanocatalyst and bio-oil production - Bahkali A.H.; Syed A.; Elgorban A.M.; Abdel-Wahab M.A.; Srivastava N.; Kumar Gupta V. (My University, 2025)
Continuous and huge production of solid waste is among the prominent cause of environmental pollution and effective management of these wastes is one of the prime global agenda for sustainable environment. Lignocellulosic biomass is one of the major contributors of solid waste that can be efficiently valorized into biofuel. In addition, nanocatalysts play a key role to improve biomass-to-biofuel production technology and related bioprocessing. The present study focuses on the green route-enabled, sustainable preparation of Al2O3 nanoparticles from waste date ripe pulp through the sol-gel method. Systematic characterization of the newly prepared nanocatalyst has been done using different characterization tools like XRD, FT-IR, BET, SEM, and TEM to evaluate the physicochemical properties. Further, this newly fabricated θ-Al2O3 nanocatalyst has been applied to produce bio-oil from date seed under ambient conditions, and a number of diverse fatty acids have been confirmed through HRMS analysis, which may be promising for biodiesel production from this waste. © 2024 The Institution of Chemical Engineers